Epistemological Synthesis of Al-Attas and Al-Faruqi: Islamization of Knowledge, Adab, and Contemporary Decolonization of Knowledge - Zainuddin, Zainuddin; Muttaqin, Muhammad; Amir, Bakhrum; Nafisah, Ani; Paizaluddin, Paizaluddin (CV. Kalimasada Group, 2025)
This study presents a comparative analysis of the concept of the Islamization of knowledge as proposed by Syed Muhammad Naquib Al-Attas and Ismail Raji Al-Faruqi, in response to the epistemological crisis in contemporary Islamic higher education. Although both thinkers share a common vision, previous studies have inadequately explored the potential for an epistemological synthesis between their approaches. This research aims to identify their points of convergence and divergence in order to construct a relevant and applicable framework for Islamic epistemology. The study employs a qualitative methodology through library research and hermeneutic-philosophical analysis. The findings indicate that Al-Attas emphasizes metaphysical dimensions and the concept of adab, while Al-Faruqi focuses on curriculum reconstruction and institutional reform. A synthesis of their approaches offers an epistemological framework that integrates philosophical depth with practical methodology. The implications include the development of integrated curricula, interdisciplinary faculty training, and the strengthening of scientific ethics grounded in tawhid. This study contributes to the development of an authentic, transformative, and globally relevant model of Islamic education.